PENGARUH LEADER MEMBER EXCHANGE DAN QUALITY OF WORK LIFE TERHADAP KOMITMEN AFEKTIF DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Mantri dan Mandor BUMN Perhutani di KPH Kedu Selatan) - Andira Darmawanti Sukamsi; Indah Rohyani (Bajang Institute, 2026)
This study aims to investigate the effect of Leader-Member Exchange (LMX) and Quality of Work Life (QWL) on affective commitment, with job satisfaction as a mediating variable among high-risk field workers. Using an explanatory quantitative approach, a saturated sample of 56 Mantri and Mandor at Perum Perhutani KPH Kedu Selatan was established. Data collected from questionnaires were analyzed using path analysis and the Sobel test with IBM SPSS 26 software. The results prove that LMX has a positive and significant effect on both job satisfaction and affective commitment. Conversely, QWL has a dominantly positive effect on job satisfaction, but does not have a significant direct impact on affective commitment. Job satisfaction is also proven to positively affect affective commitment. Furthermore, the mediation test confirms that job satisfaction acts as a full mediator on the path from QWL to affective commitment, and acts as a partial mediator on the LMX path. These findings confirm that the provision of facilities and job security does not necessarily trigger emotional loyalty without first being converted into inner satisfaction. The managerial implications of this study recommend a reorientation of HR policies that balances the fulfillment of technical welfare with a supportive leadership touch to nurture the long-term commitment of the organization's frontline workers